Supplier Relationships, Trust, and Communication: Mediating Sustainable Procurement of Company Performance - Chintya Kharina; Nasar Buntu Laulita (Universitas KH. Abdul Chalim Mojokerto, 2026)
This article discusses the influence of supplier relationships, trust, and communication on supply chain performance, with continuous procurement as a mediating variable. The main problem faced is the low performance of the supply chain caused by the lack of cooperation between companies and suppliers, where awareness in maintaining relationships such as good communication and trust is lacking. The performance of the supply chain is greatly influenced by good cooperation between suppliers and their companies, thus it will support the improvement of operational efficiency and effectiveness. Strong relationships as well as a high level of trust and effective communication with suppliers can create a positive impact on sustainable procurement which ultimately improves the performance of a company's supply chain. This research method uses a quantitative method with a survey questionnaire to collect data from companies involved in the supply chain. Recommendations for future research are to explore more deeply about sustainable procurement practices across industries and their impact on long-term performance. The results of this study are expected to provide insights for companies in managing relationships with suppliers and implementing sustainable procurement to improve supply chain performance.